ANALISIS YURIDIS KESALAHAN MATERIL AKTA NOTARIS DAN AKIBAT HUKUMNYA (STUDI PUTUSAN PENGADILAN NEGERI MEDAN NO.625/PDT.G/2013/PN.MDN) - AN NISAA’ LUBIS (PREMISE LAW JURNAL, 2016)
There are many cases related to notarial deeds claimed by third parties because one of them defaults or offends the law; causing the notary to be blamed for the material fault. As written evidence, what is stated in a notarial deed has to be acknowledged. A notary does not guarantee what is stated by persons appearing is true because he/she is not the investigator of the data handed by the parties involved. The problems of the research are how the criteria of a notarial act and the legal consequence are toward an authentic deed which has material error, how the responsibility of a notary and the legal protection to him/her are in case there is a material error in the deed he/she has made, and how the consideration of Medan District Court and the legal consequence of the material error in a notarial deed are regarding the Verdict No.635/Pdt.G/2013/PN.Mdn. Keywords: Judicial Analysis, Material Error, Notarial Deed